MINERAL COMPOSITION AND NUTRITIVE ANALYSIS OF BULBINE ABYSSINICA A. RICH. USED IN THE TREATMENT OF INFECTIONS AND COMPLICATIONS ASSOCIATED WITH DIABETES MELLITUS IN THE EASTERN CAPE PROVINCE, SOUTH AFRICA - Kibiti, Cromwell Mwiti; Afolayan, Anthony Jide (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: B. abyssinica is a succulent member of the genus Bulbine (Asphodelaceae). It occurs from the Eastern Cape, through Swaziland and further north to Ethiopia. The species is used in traditional medicine to treat rheumatism, dysentery, bilharzia, cracked lips and diabetes. The tea leaf is used to treat cough, vaginal and bladder problems. Whereas B. abyssinica has ethno medicinal value, not much data concerning its phytonutrient, macro and micro element composition can be found in literature. Materials and Methods: Therefore, the present study was undertaken to determine the nutritional quantitative composition of the plant using standard procedures. Results: The proximate analysis revealed the carbohydrate, crude fibre, moisture, ash, crude protein and crude fat contents as 74.8%, 8.9%, 8.8%, 8%, 7.7% and 0.6%, respectively. The species showed high levels of oxalates and phytic acids, moderate levels of alkaloids, flavonoids, saponins and phenols, while tannins were in low levels. Vitamin A, C and E contents were 12, 12.3 and 22.1 mg/100g, respectively. Amongst the mineral elements investigated, potassium and calcium were in high levels. Magnesium, iron, sodium, aluminium and phosphorus were moderately present, while manganese, zinc and copper where in low amounts. These vitamins and mineral elements were within their recommended daily allowance in humans. Conclusion: The amount of these phytochemicals suggests the plant can serve as nutritional supplements which are vital in maintaining good health status. These findings also suggest the potential role of B. abyssinica in the treatment of infections and some chronic diseases, especially diabetes mellitus.